2011
DOI: 10.1007/s12678-011-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Surface Structure of Pt(100) and Pt(110) on the Oxidation of Carbon Monoxide in Alkaline Solution: an FTIR and Electrochemical Study

Abstract: The electrochemical oxidation and infrared spectral features for carbon monoxide adsorbed on Pt(100) and Pt(110) in 0.1 M NaOH were studied as a function of the annealing/ cooling treatment with the objective to establish the influence of the platinum surface site geometry and the role of surface order in the electro-oxidation of CO on these two surfaces. Two common cooling methods (Ar and H 2 /Ar atmospheres) were employed for both surface electrodes. Additionally, CO cooling and I 2 vapour cooling methods we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…As potassium specific adsorption becomes more favorable as pH is increased, the simulated voltammograms with coadsorbed K* represent the expected CVs in an alkaline electrolyte. These CVs compare very well with those experimentally measured in 0.1 M KOH. ,,, While we predict the competitive adsorption of hydrogen and hydroxide in an alkaline solution on Pt(110) at a slightly higher potential, 0.35 V RHE , than what is measured experimentally, 0.28 V RHE, we predict the location of the competitive adsorption peak on Pt(100) very well, 0.41 vs ∼0.4 V RHE measured experimentally . More importantly, we capture the shift with pH very well between CVs measured in 0.1 M HClO 4 and 0.1 M KOH; for Pt(110) we calculate a shift of 0.155 V RHE compared to ∼0.15 V RHE ; for Pt(100) our calculated shift of 0.09 is a little less than what is measured experimentally, ∼0.13 V RHE .…”
Section: Resultssupporting
confidence: 83%
“…As potassium specific adsorption becomes more favorable as pH is increased, the simulated voltammograms with coadsorbed K* represent the expected CVs in an alkaline electrolyte. These CVs compare very well with those experimentally measured in 0.1 M KOH. ,,, While we predict the competitive adsorption of hydrogen and hydroxide in an alkaline solution on Pt(110) at a slightly higher potential, 0.35 V RHE , than what is measured experimentally, 0.28 V RHE, we predict the location of the competitive adsorption peak on Pt(100) very well, 0.41 vs ∼0.4 V RHE measured experimentally . More importantly, we capture the shift with pH very well between CVs measured in 0.1 M HClO 4 and 0.1 M KOH; for Pt(110) we calculate a shift of 0.155 V RHE compared to ∼0.15 V RHE ; for Pt(100) our calculated shift of 0.09 is a little less than what is measured experimentally, ∼0.13 V RHE .…”
Section: Resultssupporting
confidence: 83%
“…Table presents a summary of all these data. Considering the structure of the surface, it was previously observed that, on (100) facets in alkaline solution (0.1 M NaOH), , bridge-bonded CO dominates on a Pt(100) basal plane.…”
Section: Resultsmentioning
confidence: 99%
“…From the surface science knowledge, the different behaviors of Pt(110) CVs were suspected to be due to the varied populations of (1 × 1) and (1 × 2) domains ((1 × 2) is a typical missing row reconstruction of (1 × 1) under surface science conditions) . For hydrogen cooled electrode, the CV at the H upd region shows two peaks at 0.12 and 0.25 V vs RHE, which should be related to the missing row (1 × 2) structure reconstruction since it was indeed observed by using in situ Fourier transform infrared technique and CV. However, multiple reversible electrosorption peaks centered at 0.145, 0.20, and 0.25 V vs RHE for the CO-cooled electrode are not assigned properly due to the appearance of the additional 0.20 V peak, where the surface is initially dominated by the (1 × 1) surface domain. ,, To clarify the experiment, an atomic level knowledge of the electrode is required, which involves complex hydrogen adsorption/desorption states at different local atomic structures, such as terraces, steps, and reconstructed sites , and the sites with coadsorption of anion and cation. , …”
Section: Introductionmentioning
confidence: 84%